Challenges in the implementation of the upgrading of informal settlements programme (UISP): an evaluation of two Gauteng Metropolitan Municipalities - Bafo, Pumla Sithandiwe (My University, 2016)
One of the most critical housing issues of concern today is the continued proliferation of informal settlements and the failure of government to meet the housing demand. Party to the United Nations Millennium Development Goals, which includes the goal to improve the lives of at least 100 million slum dwellers by 2020 introduced the Upgrading of Informal Settlements Programme (UISP). Despite the introduction of this new paradigm shift, its implementation has been minimal. This report investigates: if metropolitan municipalities are implementing the programme and the underlying challenges faced by municipalities in implementation. The study points to the importance of the 5 crucial variables: Policy content, context, commitment, capacity and coalitions and clients in implementation. The research made use of qualitative methods, which included literature review of books, academic and media articles. The people interviewed comprised of political leaders, both senior and junior officials of the Municipalities and former employees of the City of Johannesburg, all tasked with informal settlement intervention implementation. The data collected was analysed using cross comparison between the various municipal officials’ responses, evaluating officials’ interpretation against policy interpretation, analysing the complexities of the policy, teasing out the comparisons, summarising data in order to make sense of what has been collected, identifying and classifying key concepts that emerge from the interviews, sorting data obtained through semi-structured interviews into smaller units in order to interpret how the two municipalities interpret and implement the programme (Gray, 2004:210), categorising data in order to understand the funding mechanisms used by the various municipalities and using the key concepts for descriptive analysis. Based on the findings of the study it was concluded that the Municipality has not been implementing UISP as per the housing code, however it has been utilising formalisation as an intervention in its informal settlement. The findings of the current study provide answers to the guiding research questions on whether municipalities are implementing UISP and interventions within the two municipalities. The conclusion is that both municipalities are not implementing UISP. However they have their own interventions which are biased toward the realities of project managers rather than the organized informal settlement communities thus disconnecting from the premise of UISP. The envisaged limitation was getting hold of municipal officials as this research was conducted in the first quarter of the new financial year and municipal officials were engaged in strategic meetings. This is an unfortunate limitation that could not be avoided therefore interviews especially in EMM were not carried out as planned but as and when the contact persons were available. This resulted in only 5 officials being interviewed as compared to the anticipated number. Secondly, one of the municipalities that the research was conducted on was reluctant to give out information.
A Research Report submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, in fulfilment of the requirements for the degree of Master of the Built Environment in Housing. APRIL 2016
Keywords: City planning--South Africa--Gauteng; Squatter settlements--South Africa--Gauteng; Housing--South Africa--Gauteng